Hubungan Keterampilam Komunikasi Interpersonal dengan Tingkat Kepercayaan Diri - Amalia Mawaddah; Nur Wisma (Islamic Counseling: Jurnal Bimbingan dan Konseling Islam, 2023)
One aspect of improving communication is self-confidence and relationships between individuals. This research aims to determine the relationship between interpersonal communication and self-confidence in students at SMP Negeri 17 Palembang. This research is a quantitative correlational research with a research population of 272 and a research sample of 72 which was determined using a simple random sampling technique using the Slovin formula. The data collection technique in this research uses a psychological scale. The data collection method in this research is an interpersonal communication scale and a self-confidence scale obtained through direct distribution of instruments. Data analysis in this research used Pearson Product Moment. The results of data analysis show that the level of interpersonal communication is in the medium category with a percentage of 34% (25 students) and the level of self-confidence is in the low category with a percentage of 32% (23 students). Then the correlation coefficient (r) = 0.792 and sig. (2-tailed) 0.000 or > 0.05, which means there is a significant positive relationship between interpersonal communication and self-confidence. Thus, it can be concluded that there is a positive relationship between interpersonal communication and students' self-confidence at SMP Negeri 17 Palembang.